2001
DOI: 10.1177/153537020122601110
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein Peptic Hydrolysates Stimulate Cholecystokinin Release via Direct Sensing by Rat Intestinal Mucosal Cells

Abstract: We previously demonstrated that a peptic hydrolysate of guanidinated casein strongly stimulates exocrine pancreatic secretion in chronic bile-pancreatic juice-diverted rats and cholecystokinin (CCK) release from dispersed rat intestinal mucosal cells. These results reveal that the chemically modified protein hydrolysate stimulates CCK secretion and Increases pancreatic secretion by a luminal trypsin-independent direct action on the small Intestine. In the present study, we examined the direct effect of peptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 30 publications
(26 reference statements)
2
31
0
Order By: Relevance
“…10,13,14,19) The finding from CCK secretion study that PorkP, ChickP, and BconP released CCK with direct application to STC-1 cells also supports the previous findings. Conversely, it has been shown that endogenous CCK-releasing peptides also stimulate CCK release from STC-1 cells.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…10,13,14,19) The finding from CCK secretion study that PorkP, ChickP, and BconP released CCK with direct application to STC-1 cells also supports the previous findings. Conversely, it has been shown that endogenous CCK-releasing peptides also stimulate CCK release from STC-1 cells.…”
Section: Discussionsupporting
confidence: 78%
“…[10][11][12] Previously we found that intraduodenal infusion of a peptic hydrolysate of soybean -conglycinin, -conglycinin peptone (BconP), suppresses food intake through this CCK release. 13,14) It has been suggested that binding of dietary proteins or peptides to the rat small intestinal brush-border membrane (BBM) is an integral part of a common sensory mechanism to release CCK. 15) We found that appetite suppression by BconP corresponds to the binding ability of this peptone to the rat small intestinal BBM as well as stimulation of CCK release directly from rat isolated dispersed intestinal mucosal cells.…”
mentioning
confidence: 99%
“…8) However, we and other researchers have found that dietary protein/peptide acted directly on CCK-producing EECs to stimulate CCK release and suppress appetite independently from endogenous CCK-releasing peptides. [9][10][11][12][13] These findings were further supported by the result that peptones stimulated CCK secretion in CCK-producing murine enteroendocrine STC-1 cell line. [14][15][16][17][18] We have previously demonstrated that an intraduodenal infusion of peptides from a peptic hydrolysate (peptone) of soybean -conglycinin suppressed the food intake by duodenally-cannulated rats and directly stimulated CCK release from the EECs.…”
supporting
confidence: 75%
“…10,11) We later showed that an orogastric administration of pork peptone under more physiological conditions suppressed the appetite of rats by the release of CCK from the EECs. 14) We have previously found several CCK-releasing and appetite-suppressing peptic digests from various protein sources, [9][10][11]14,15) although the effect of hydrolysates obtained by proteases other than pepsin on CCK release and appetite suppression have not been studied. Furthermore, the bitter oro-sensory characteristic of peptic hydrolysates appeared to be less suitable for oral consumption in human applications.…”
mentioning
confidence: 99%
“…Several studies have shown that peptides and FA can use an external receptor to induce CCK secretions (Choi et al, 2007, Tanaka et al, 2008, Shah et al, 2011. In vivo and in vitro studies indicate that proteins increase CCK secretion (Beucher et al, 1994, Cordier-Bussat et al, 1997, Nishi et al, 2001). This effect is further improved when proteins are hydrolysed, however individual amino acids do not contribute to CCK release (Liddle et al, 1985).…”
Section: Cholecystokinin (Cck) Is a Peptide Hormone Reported To Have mentioning
confidence: 99%